Modeling of hydrocarbon systems and quantitative assessment of the hydrocarbon potential of Eastern Arctic seas - E. A. Lavrenova; Yu. V. Shcherbina; R. A. Mamedov (Известия высших учебных заведений: Геология и разведка)
Background. Three prospective sedimentary complexes — Aptian-Upper Cretaceous, Paleogene and Neogene — are predicted in the waters of the Eastern Arctic seas. Here, the search for oil and gas is associated with harsh Arctic conditions at sea, as well as with high geological risks and significant expenditures under the conditions of poor knowledge of the region. In this regard, the localisation of prospecting drilling objects and the assessment of the geological risks of deposit discovery should be carried out.Aim. To assess geological risks and to determine the probability of discovering oil and gas fields, as well as to identify prospective areas for licensing and exploration in the water areas of the Eastern Arctic.Materials and methods. Structural and heat flow maps along with the results of geochemical analysis, as well as typical terrestrial sections were used as initial materials. Using the method of basin analysis, the modelling of generation-accumulation hydrocarbon systems (GAHS) and the quantitative assessment of its hydrocarbon potential in the Eastern Arctic water area was carried out. The assessment of geological risks and the probability of field discovery was performed using the conventional methodology widely applied by oil companies.Results. The GAHS modelling using a variation approach showed that, regardless of the kerogen type, with average values of Сorg in sediments, potential oil-and-gas source strata (OGSS) were capable of saturating the prospective objects with hydrocarbons. The “OGSS assessment” factor was determined as “encouraging” (0.7). Active geodynamic regime and the manifestation of several folding phases within the study area provided favourable conditions for the formation of anticlinaltraps in sedimentary basins. However, the cap rock quality rating was assessed as “neutral” (0.5). The overall risk for the “Trap assessment” factor was estimated based on the minimum criterion of 0.5.Conclusion. The most prospective areas recommended for licensing were selected, and the recommendations for further geological exploration work in these areas were given in order to clarify their hydrocarbon potential and reduce geological risks.